DA TERCEIRA REVOLUÇÃO INDUSTRIAL À PRODUÇÃO ENXUTA SEU IMPACTO NA INDÚSTRIA DE AUTOPEÇAS CASO: MAHLE METAL LEVE S/A - Arsenio, Evandro Pereira (2008)
The present dissertation has the goal to verify the reasons which Metal Leve relinquished share-holder majority to an international competitor and to compare the existent situation in the time of denationalization and the situation in the new controlling company Mahle Metal Leve S.A. in production form and administration, after the reorganization of the productive restructuring. That process of productive internationalization r4sult in modification in the company restructuring of the production and of the administration and occasion a new virtous circle and represent the bases of a new economical growth, with a strategic project of long term, associated to his economical power, managerial capacity and his tradition. The study is based in a group of information about the two moments, focusing the financial results, managerial aspects, leadership, competitive capacity and the evolution to the long of those of the two compared moments. Concluding that not just the phenomenon of the globalization of the international economy turned inevitable the cession of the shareholders capital. But, it also lacked strategic vision to perceive the changes that unavoidably happened his turn. The new controlling Mahler Metal Leve brought a new managerial competence that resulted in increased of productivity and it improved his competitiveness.